Alpha-amanitin-resistant transcription units in trypanosomes: a comparison of promoter sequences for a VSG gene expression site and for the ribosomal RNA genes. - Zomerdijk, J C (1991)
Transcription of the predominant surface antigen genes in Trypanosoma brucei is unusual in its resistance to the RNA polymerase inhibitor alpha-amanitin, a property typical for rDNA transcription in eukaryotes. Transcription of most other protein-coding genes in trypanosomes is sensitive to alpha-amanitin. To investigate whether RNA polymerase I, the polymerase that transcribes rRNA genes, can give rise to functional mRNAs in trypanosomes, we have fused the putative promoter of the T.brucei rRNA genes to the chloramphenicol acetyl transferase (CAT) gene and determined CAT activity after transient expression of chimeric constructs in procyclic trypanosomes. We show here that the rRNA promoter yields the same high CAT activity as the promoters for the two predominant surface antigen genes of trypanosomes, the Variant-specific Surface Glycoprotein (VSG) gene of bloodstream trypanosomes and the procyclin gene of insect-form trypanosomes, both of which are also transcribed by an alpha-amanitin-insensitive RNA polymerase. RNA polymerase I of trypanosomes seems therefore able to synthesize pre-mRNAs that are effectively processed into translatable mRNAs. Dissection of the promoter segments showed the minimal elements for a VSG gene expression site promoter to be confined to a segment of -60 to +77 bp, overlapping the most 5' putative transcription start sites as determined in vivo by RNase protection experiments. For the ribosomal promoter region a segment of -258 to +200 bp relative to the putative transcription start site was sufficient for maximal CAT activity. There is a precise requirement for specific nucleotides at the rRNA transcription start site. We detect no homology between the sequences required for promoter function of the three alpha-amanitin-resistant transcription units, rRNA, VSG and procyclin (parp) genes. This suggests that the sequence-specific recognition of these promoters either occurs by common factors detecting sequence homologies that escape us, or by separate factors that bind to different DNA sequences but interact with a common alpha-amanitin-resistant RNA polymerase.